2012
DOI: 10.14742/ajet.883
|View full text |Cite
|
Sign up to set email alerts
|

Understanding student perceptions and motivation towards academic blogs: An exploratory study

Abstract: The success of academic blogs depends on the participation and engagement of students. Taking an exploratory approach, this study aims to develop a better understanding of the perceptions of student teachers towards academic blogging, and the factors that motivate them to write academic blogs voluntarily. Drawing on data gathered from questionnaires, interviews, and content analysis of blog posts, the study reveals a set of mediating factors in individual, social and academic dimensions, among which students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…The motivating and inhibiting factors for students' engagement with TPNW were also investigated. Resonant of Deng and Yuen (2012), our study revealed that the students' online participation was influenced by a set of individual, social and academic elements. Some students considered online sharing intrinsically rewarding as it enabled the contributors to gain recognition for their effort and hence boosted their confidence.…”
Section: Figure 2 Roles Of Tpnw and Facebookmentioning
confidence: 78%
“…The motivating and inhibiting factors for students' engagement with TPNW were also investigated. Resonant of Deng and Yuen (2012), our study revealed that the students' online participation was influenced by a set of individual, social and academic elements. Some students considered online sharing intrinsically rewarding as it enabled the contributors to gain recognition for their effort and hence boosted their confidence.…”
Section: Figure 2 Roles Of Tpnw and Facebookmentioning
confidence: 78%
“…A few studies also showed that blogs [59] and multimedia formats (in particular, video storytelling) [60] are effective media for documenting personal experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, Web 2.0 applications, and especially blogs, wikis, e-portfolios, social media, podcasting, social networking etc., have received intense and growing educational interest, with uses including diverse learning groups, from primary and secondary education (Tse, Yuen, Loh, Lam, & Ng, 2010, Sheehy, 2008Woo, Chu, Ho, & Li, 2011;Angelaina & Jimoyiannis, 2011) to higher education (Bolliger & Shepherd, 2010;Ching & Hsu, 2011;Deng & Yuen, 2011;Roussinos & Jimoyiannis, 2011;Yang, 2009;Zorko, 2009), vocational training (Marsden & Piggot-Irvine, 2012) and teachers' professional development (Doherty, 2011;Wheeler, & Wheeler, 2009;Wopereis, Sloep, & Poortman , 2010).…”
Section: Introductionmentioning
confidence: 99%